Kesiapsiagaan dan Kapasitas Tanggap Darurat Layanan Medis Gawat Darurat (Emergency Medical Services) terhadap Bencana: Scoping Review - Rati Awaliah; M. Dio Triyoga; Nabila Chairunissa; Nazla Nur Riastini; Ririn Zuhairini (PPNI UNIMMAN, 2025)
Disasters are global phenomena that continue to increase in both frequency and impact, posing serious challenges to health systems worldwide. One of the crucial components in disaster management is the preparedness of Emergency Medical Services (EMS) during the pre-hospital phase, which determines the speed and effectiveness of the initial medical response. However, multiple studies indicate that EMS preparedness and response capacity remain suboptimal, particularly in areas such as personnel training, intersectoral coordination, communication systems, infrastructure, and policy support. This study aims to map the preparedness and emergency response capacity of EMS in disaster situations using a scoping review approach. The research follows the methodological framework of Arksey and O’Malley (2005), which includes formulating research questions, conducting literature searches, selecting relevant studies, extracting data, and synthesizing findings. Literature searches were conducted through PubMed, ScienceDirect, Cochrane Library, and Google Scholar databases. From 114 identified records, 12 studies met the inclusion criteria. The review reveals that EMS disaster preparedness varies across countries. The main factors influencing EMS response capacity include: (1) training and competency development of EMS personnel, (2) effectiveness of interagency coordination and communication, (3) availability of medical facilities and infrastructure, (4) national policy and system support, and (5) the use of technology to enhance response efficiency. This scoping review underscores the need for stronger national policies, improved cross-sectoral coordination, and sustainable capacity-building programs to enhance the effectiveness of EMS in disaster response, particularly in developing countries such as Indonesia.